Productivity of cattle treated with cypermethrin 'pour-on' insecticide to control tsetse in southwest Ethiopia - Mulatu, W.; Rowlands, G.J.; D'Ieteren, G.D.M.; Leak, S.G.A.; Nagda, S.M. (OAU/ISCTRC, 1995)
Approximately 90 village Ethiopian Highland Zebu cattle at Gullele in southwest Ethiopia were ear-tagged in March 1986 and they and their offspring monitored monthly until February 1996. In January 1991 a tsetse control campaign began using a synthetic pyrethroid cypermethrin pour-on applied monthly to cattle. This resulted in reductions of 95 percent in mean relative densities of tsetse and biting flies from 1992 to 1995. A cost recovery scheme was introduced in December 1992, and thereafter, farmers paid for treatment. Cattle from neighbouring herds not affected by this campaign were also monitored and these were used where possible as statistical controls. Tsetse control resulted in a reduction of 64 percent prevalence of trypanosomal infections and 50 percent in the number of treatments of diminazene aceturate given to cattle detected parasitaemic or showing clinical signs of trypanosomosis. Associated with these reductions there were significant increases of 20 percent in mean calf growth rate over the wet season (P<0.05) and an average decrease of 50 percent in abortion rate and calf mortality to 12 months of age (P<0.05). There was an increase of 37 percent in the ratio of live calves under 12 months of age to cows (from 0.49 = 0.03 to 0.66 = 0.08 (P<0.05)) and an average increase of 6 percent in adult body weight (P<0.05 for cows; P<0.01 for oxen). Packed red cell volume was significantly increased only in adult males. Despite the increase in calf growth rate over the wet season there was however, no significant increase in mean body weight at 12 months of age. Calving rate did not change significantly. The major benefit of tsetse control appears to have been the increase in numbers of cattle raised and new owners settling in the area. Generally, however, the significances of the results were difficult to substaniate statistically.